Tajzi`ah al-Quran: Kajian Terhadap Periwayatan al-Dani, al-Sakhawi dan al-Safaqusi serta Amalan Semasa Percetakan Mushaf: Fragmentation of The Quran: A Study on al-Dani, al-Sakhawi, al-Safaqusi’s Narration and The Current Practice of Printed Mushaf - Ahmad, Abd Muhaimin (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
The tajzi`ah (fragmentation) plays a role of quantifying the amount of reading and memorizing the Quran by juz (part or division). In classical and modern writings of Muslim scholars, there are different opinions about tajzi`ah the Quran that it has effect to printing of the Quran. Thus, this study will analyze some classical and medieval Quranic scholars’ opinions in tajzi`ah the Quran with particular reference to al-Bayan fi `Addi Ayi al-Quran of al-Dani, Jamal al-Qurra 'wa Kamal al-Iqra' of al- Sakhawi and Ghaith al-Naf 'fi al-Qira`at al-Sab' of al-Safaqusi. Subsequenly, their opinions will be compared with the current practice of the tajzi'ah in the Mushaf al-Quran printed by Mujamma’ Malik al-Fahd in Medina. This qualitative study was conducted using content analysis methods through descriptive and comparative analysis of texts in accomodating scholars’ opinions in tajzi`ah of the Quran along with the current practices in printed copy of the Quran. In this comparative analysis, most of the tajzi'ah (20 juz’) of the Mushaf Medina in accordance with those three scholars’ tajzi’ah. However, some of these tajzi’ah were not agreed by them, and the tajzi`ah of Mushaf Medina was only in agreement with one of them (9 juz’). The study also found that one tajzi`ah has not been agreed by these three scholars as the printed Mushaf Medina was not in similarity by every possible means.